Ocorrência de parasitos gastrointestinais em cães de Cuiabá, Mato Grosso - Souza, Cristiane Trevisan Viana de (2022)
Gastrointestinal parasitism by helminths and protozoa poses risks to animal and human health owing to clinical changes and transmission of zoonoses. Thus, the present study aimed to verify the occurrence of gastrointestinal parasites in dogs from the municipality of Cuiabá, Mato Grosso, Brazil, using coproparasitological tests. From June 2021 to April 2022, stool samples were collected from domestic dogs at the Veterinary Hospital and Animal Protection Shelters in the Cuiabá municipality. A semistructured questionnaire was applied to the owners and those responsible for the shelters to analyse the factors associated with gastrointestinal parasitism. A total of 353 stool samples were collected and subjected to Willis-Mollay, Faust and Hoffman, and Pons and Janer parasitological techniques. Data were analysed using the chisquared test and exploratory factorial analysis. The occurrence of gastrointestinal parasitism was 22.66% and the parasites found alone or in mixed infections were Ancylostoma spp., Trichuris vulpis, Toxocara spp., Dipylidium caninum, Cystoisospora spp., Giardia duodenalis, and coccidia. Among these, the most frequent were Ancylostoma spp. and Trichuris vulpis. The risk factors associated with the infection were being from the shelter population (p = 1,798-16), not being of a defined breed (p = 3,250-7 ), being an adult (p = 0,004), living with other animals (p = 0,007), and having a dull fur (p = 0,024). The gastrointestinal parasites with zoonotic potential found alert to the risk of human infection, and it is necessary to adopt control and prevention measures in the context of one health.